Implementasi Load Balancing dan Failover 2 ISP pada Mikrotik Menggunakan Metode Equal Cost Multipath (ECMP) - Habibullah, Maulana Ahmad; Pamuji, Madadina Adilah; Yuliastuti, Gusti Eka; Sulaksono, Danang Haryo; Ariansyah, Fernando Yoga (Institut Teknologi Adhi Tama Surabaya, 2025)
Implementing load balancing and failover on computer networks is important, especially on networks that have a high traffic load. Load balancing serves to distribute traffic loads across several internet links, thereby improving network performance. In this research, load balancing and failover 2 ISP were implemented on the SMA Negeri 11 Surabaya network using a proxy with the Equal Cost MultiPath (ECMP) method. The ECMP is a load-balancing method that divides traffic evenly across all available internet links. The results of research conducted at SMA Negeri 11 Surabaya indicated that the load balancing and failover for two ISPs on MikroTik using the ECMP method could run well. They obtained an average throughput of 124.01 Mbps, a packet loss of 0%, and a QoS index of 4. Furthermore, failover could maintain network availability when one of the internet links experienced problems.